Spraying alginate oligosaccharide improves photosynthetic performance and sugar accumulation in citrus by regulating antioxidant system and related gene expression - Li, Zhiming; Duan, Songpo; Lu, Bosi; Yang, Chunmei; Ding, Hanqing; Shen, Hong (Frontiers in Plant Science, 2023)
Alginate oligosaccharides (AOS) are functional substances in seaweed extracts that regulate crop quality and stress tolerance. In this paper, the effects of AOS spray application on the antioxidant system, photosynthesis and fruit sugar accumulation in citrus was investigated through a two-year field experiment. The results showed that 8-10 spray cycles of 300-500 mg L-1 AOS (once per 15 days) increased soluble sugar and soluble solid contents by 7.74-15.79% and 9.98-15.35%, respectively, from citrus fruit expansion to harvesting. Compared with the control, the antioxidant enzyme activity and the expression of some related genes in citrus leaves started to increase significantly after the 1st AOS spray application, while the net photosynthetic rate of leaves increased obviously only after the 3rd AOS spray cycle, and the soluble sugar content of AOS-treated leaves increased by 8.43-12.96% at harvest. This suggests that AOS may enhance photosynthesis and sugar accumulation in leaves by antioxidant system regulation. Moreover, analysis of fruit sugar metabolism showed that during the 3rd to 8th AOS spray cycles, AOS treatment increased the activity of enzymes related to sucrose synthesis (SPS, SSs), upregulated the expression of sucrose metabolism (CitSPS1, CitSPS2, SUS) and transport (SUC3, SUC4) genes, and promoted the accumulation of sucrose, glucose and fructose in fruits. Notably, the concentration of soluble sugars in citrus fruits was significantly reduced at all treatments with 40% reduction in leaves of the same branch, but the loss of soluble sugars in AOS-treated fruits (18.18%) was higher than that in the control treatment (14.10%). It showed that there was a positive effect of AOS application on leaf assimilation product transport and fruit sugar accumulation. In summary, AOS application may improve fruit sugar accumulation and quality by regulating the leaf antioxidant system, increasing the photosynthetic rate and assimilate product accumulation, and promoting sugar transfer from leaves to fruits. This study shows the potential application of AOS in the production of citrus fruits for sugar enhancement.